ZIF-8/ Co-C3N4-GNR/MXene nanocomposites: A novel electrode material with excellent electrochemical properties for supercapacitors - Rozhin Darabi; Mehdi Shabani-Nooshabadi (Alexandria Engineering Journal, 2025)
The combination of MXenes with metal-organic frameworks (MOFs), along with the incorporation of graphene nanoribbons (GNRs), results in highly promising materials for energy storage applications. Owing to their unique structure, high porosity, and strong interfacial connectivity, these composites exhibit excellent mechanical stability and enable rapid ion and electron transport. The synergistic integration of MXenes, MOFs, and GNRs with the excellent electrical conductivity and 2D structure of MXenes, high porosity and tunable surface area of MOFs, and the mechanical strength and flexibility of GNRs, provides the composite with a high surface area, excellent electrical conductivity, and robust structural stability. In this study, we report a multi-component nanocomposite, ZIF-8/Co-C₃N₄-GNR/MXene, synthesized using a simple method. Key factors influencing capacitance, power density, and energy density were optimized to achieve superior electrochemical performance. According to our knowledge, this is the first synthesis of this specific composite structure, offering strong potential for advanced supercapacitor design. Electrochemical performance was evaluated using cyclic voltammetry (CV), galvanostatic charge–discharge (GCD), and electrochemical impedance spectroscopy (EIS). The ZIF-8/Co-C₃N₄-GNR/MXene composite demonstrated a high specific capacitance of 1125 F·g⁻¹ at a current density of 1 A·g⁻¹ , with an energy density of 100 Wh·kg⁻¹ and a power density of 400 W·kg⁻¹ . Furthermore, it maintained approximately 87 % of its initial capacitance after 10,000 cycles, highlighting the nanocomposite's strong potential as an electrode material for high-performance asymmetric supercapacitors and its suitability for next-generation electronic devices.